Test excavation of the “pseudo-ditch” system of the Late Neolithic settlement complex at Öcsöd-Kováshalom on the Great Hungarian Plain: Preliminary report - Füzesi, András; Rassmann, Knut; Bánffy, Eszter; Hoehler-Brockmann, Hajo; Kalla, Gábor; Szabó, Nóra; Szilágyi, Márton; Raczky, Pál (Dissertationes Archaeologicae, 2021)
In 2018, the RGK’s research team led by Knut Rassmann undertook the magnetometer survey of the Late Neolithic site of Öcsöd-Kováshalom over a roughly 65 ha large area. An enclosure system of three concentric semi-circular ditches was detected around the tell-like mound that formed the core of the settlement. In order to resolve these issues, we organised a small field school excavation with the support of the RGK and with the participation of the archaeology students of the ELTE Institute of Archaeological Sciences between July 13 and 25, 2020. We opened an 8×2 m trial trench across the north-eastern part of the innermost ditch appearing on the magnetogram. We uncovered a ditch segment with a V-shaped cross-section, a width of 315 cm and a depth of 295 cm. We recovered a total of 17,430 finds with a weight of 194.4 kg (pottery sherds, daub, animal bones, bone tools, chipped and polished stone implements, quern stones, mussels, and ochre). In our preliminary report, we made a reconstruction of infilling process based on the quantitative distribution of the finds (frequency and weight data) and the different characteristics of the fill layers.